AB0440 The Impact of Patient Characteristics and Past Treatment History on the Evolution of Functional Disability in RA Patients Treated with Abatacept. A Pan-European Analysis of RA Registries. (9th June 2015) - Finckh, A.; Iannone, F.; Neto, D.; Hernández, M.; Lie, E.; Canhão, H.; Pavelka, K.; Turesson, C.; Mariette, X.; Gottenberg, J.-E.; Hetland, M.L.
Abstract : Background: Patient recorded outcomes (PROs) are increasingly used to include patients' (pts) perspective when assessing outcomes in rheumatoid arthritis (RA). One of the most established PROs in RA is the health assessment questionnaire disability index (HAQ), assessing pts function in daily life. Objectives: The objective of this study is to analyze the change in functional disability after initiation of Abatacept (ABA) treatment in RA pts and study prognostic factors of good functional response to treatment. Methods: This is an observational cohort analysis of 9 prospective, longitudinal, European cohorts of RA pts (ARTIS (Sweden), ATTRA (Czech Republic), BIOBADASER (Spain), DANBIO (Denmark), GISEA (Italy), NORDMARDS (Norway), ORA (France), Rheuma.pt (Portugal) and SCQM (Switzerland)). We included all RA pts treated with ABA, who had sequential HAQ assessments (>2) after ABA initiation. The primary end point was the longitudinal evolution of HAQ. A secondary endpoint was the proportion of patients reaching the "Minimally clinically important difference" (MCID >0.22) for the HAQ. Since HAQ is a repeated measure, we performed a Mixed Linear Model. The model included sex, age, disease duration, DAS28 at baseline, previous inadequate responses to biotherapies (BIO-IR), number prior conventional DMARDs and seropositivity (anti-CCP and/or Rheumatoid Factor) as covariates. Results: We included 1807 pts contributing 3045 patient-years of follow-up. Pts were mostly female (80%), with a mean age of 57 yrs (SD: 13), long disease durations (mean 10.3 yrs, SD: 7.1), and active disease at baseline (mean values for DAS28: 5.0 (SD: 1.4), ESR: 31 mm/hr (SD: 24), HAQ: 1.3 (SD: 0.7)). Most pts had experienced a prior BIO-IR (median number of BIO-IRs: 2, IQR 1-3), 74% were anti-CCP positive and 80% RF positive. HAQ scores at baseline were significantly lower in older pts, in females, in pts with higher disease activity and in pts having experienced more prior BIO-IRs. Although women reported more functional disability at baseline, the improvement in HAQ over time was similar in men and women (p=0.84), with 42% of male pts reaching the MCID for the HAQ compared to 40% in female pts at 1 year. Compared to the rest of the patient population, older pts (>65 years), pts with longer disease durations and pts having experienced multiple BIO-IRs improved their functional capacity (HAQ) significantly less over time (p<0.001). Conclusions: The improvement in function (HAQ) after ABA initiation is strongly influenced by pts characteristics and by their prior treatment history, with lesser response in older pts, with longer disease durations and with a history of multiple BIO-IRs. These parameters may be useful to the clinician when discussing new treatment options and helping pts to have realistic expectations. Furthermore, differences in these parameters need to be taken into account in indirect comparisons of different biologic DMARDs in observational studies. Disclosure of Interest: A. Finckh Grant/research support from: Unrestricted research grant from BMS, F. Iannone: None declared, D. Neto: None declared, M. Hernández: None declared, E. Lie: None declared, H. Canhão: None declared, K. Pavelka: None declared, C. Turesson: None declared, X. Mariette: None declared, J.-E. Gottenberg: None declared, M. Hetland: None declared